Comparison of bypassing agents in patients on emicizumab using global hemostasis assays. Issue 1 (27th November 2020) - Kizilocak, Hande; Marquez‐Casas, Elizabeth; Phei Wee, Choo; Malvar, Jemily; Carmona, Roxana; Young, Guy
Abstract: Introduction: Emicizumab is a humanized bispecific monoclonal antibody licensed for patients with severe haemophilia A with and without inhibitors. Management of breakthrough bleeding in patients with inhibitors on emicizumab involves episodic treatment with bypassing agents (BPA), activated prothrombin complex concentrate (aPCC) or recombinant activated factor VII (rFVIIa). Thrombotic events and thrombotic microangiopathy were reported when patients on emicizumab received concomitant aPCC at relatively high doses yet such events were not reported with rFVIIa. We studied the effect of spiking various concentrations of BPA on plasma taken from patients on emicizumab. Material and Methods: Eleven patients with severe haemophilia A with inhibitors who are on emicizumab were recruited to participate. Blood samples drawn from patients were spiked in vitro with varying concentrations of aPCC and rFVIIa. All samples were tested utilizing global haemostasis assays, thromboelastography and thrombin generation assay. Results: Thrombin generation increased with higher concentrations of spiked BPA with a normalized endogenous thrombin potential at a concentration of 0.05 IU/ml and 4 mcg/ml for aPCC and rFVIIa, respectively. Concentrations of aPCC in the range of licensed dosing led to excessive thrombin generation. Thromboelastography was not sufficiently sensitive. Conclusion: Due to the known thrombotic complications when emicizumab is used in conjunction with aPCC, there has been a large‐scale abandonment of the use of aPCC in patients on emicizumab. However, it is possible that aPCC can be used safely with emicizumab albeit with lower doses than are typically prescribed. It would be important to test this hypothesis in a clinical study.